Nikt nie dotknął strun harfy z większym wdziękiem”: Pierwszy poemat pochwalny napisany do Macieja Kazimierza Sarbiewskiego - Hulsenboom, Paul (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
The first eulogy addressed to the Polish poet Mathias Casimirus Sarbievius, printed in two different versions in 1630 and 1632, was written by Gilbertus Joninus, a Frenchman whose oeuvre shows he had a remarkable interest in Poland, sparked perhaps by the odes of Sarbievius, while both Jesuits were staying in Rome. In his ode to the Pole, Joninus displays a thorough knowledge of the addressee’s works, as he sums up the themes Sarbievius wrote about the most, such as the military victories of Poland’s leaders, or “the weapons of the heavenly Cupid”. Interestingly, these themes return in Joninus’ own works as well, which may imply that the Frenchman indeed was inspired by Sarbievius, much like, as Joninus writes, Horace was inspired by Melpomene. At the end of the ode, therefore, it is perhaps not surprising to find that Joninus feels the Polish Jesuit had actually surpassed his ancient example, and that he was a “not unworthy descendant of Orpheus”. Joninus’ comparison of Sarbievius with Horace, as well as his use of Hor. Od. IV, 3, would later be copied by numerous authors. What little differences there are between the 1630 and the 1632 versions of Joninus’ work mostly have to do with diversifying the author’s vocabulary, or else serve to make more sense of a given passage. The largest divergence, however, not only makes the poem refer to Hor. Od. IV, 3 more clearly, but may also have genuine implications for our reading of the text. In the second edition, as opposed to the first, Sarbievius is compared to both Horace and Melpomene, and Joninus may furthermore be alluding to another aspect of Horace’s ode, saying that the Pole is either loved in Rome, or despised there. Two years after the poem’s first edition, Joninus seems to have had an even higher opinion of his Polish colleague, and he may have added an extra level of interpretation to his ode altogether.